Cardiac magnetic resonance diastolic indices correlate with ventricular filling pressures in pediatric heart transplant recipients. (10th June 2022) - Belay, Wubishet; Godown, Justin; Chan, Kak‐Chen; Bearl, David W.; George‐Durrett, Kristen; Slaughter, James C.; Crum, Kimberly; Dodd, Debra A.; Chrisant, Maryanne; Hernandez, Lazaro; Soslow, Jonathan
Abstract: Background: Atrial and ventricular filling pressures are routinely used in pediatric heart transplant (PHTx) recipients to assess graft function. We hypothesized that cardiac magnetic resonance (CMR) diastolic indices correlate with filling pressures, providing a noninvasive method of hemodynamic assessment. Methods: Pediatric heart transplant recipients were prospectively enrolled at the time of cardiac catheterization. Pulmonary capillary wedge pressure (PCWP) and right atrial pressure (RAP) were measured. CMR included standard volumetric analysis. Filling curves were calculated by contouring every phase in the short‐axis stack. Global longitudinal and circumferential strain (GLS, GCS) were calculated using feature tracking. Atrial volumes and ejection fraction were calculated from 4‐chamber and 2‐chamber cine images. Correlations were analyzed using Spearman's Rho; modeling was performed with multivariable logistic regression. Results: A total of 35 patients with a mean age of 15.5 years were included, 12 with acute rejection. The median time post‐transplant was 6.2 years. Peak filling rate (PFR) and peak LV ejection rate/end‐diastolic volume (PER/EDV) correlated with PCWP (rho = 0.48 p = .005, and rho = −0.35 p = .046, respectively) as did GLS and GCS (rho = 0.52 p = .002, and 0.40 p = .01). Indexed maximum and minimum left atrial (LA) volume correlated with PCWP (rho = 0.41, p = .01, rho = 0.41 p = .01), and LA ejection fraction inversely correlated with PCWP (rho = −0.40, p = .02). GLS and GCS correlated with RAP (rho = 0.55, p = .001 and rho = 0.43, p = .01). A model including LV GLS and PFR estimated PCWP ≥12 mmHg with an area under the curve of 0.84. Conclusions: Cardiac magnetic resonance can be a useful noninvasive modality to assess for signs of diastolic dysfunction after PHTx.